2015
DOI: 10.14710/jitaa.40.2.115-120
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Farming Model of Small Ruminants in Deli Serdang, North Sumatra - Indonesia

Abstract: ABSTRAKPenelitian ini bertujuan untuk mengukur nilai tambah ternak kambing dan domba dengan sistem pemberian pakan cut and carry dan faktor-faktor yang mempengaruhi produktivitas ternak serta nilai tambah pemanfaatan kotoran untuk produktivitas tanaman. Penelitian dilakukan di Kabupaten Deli Serdang dengan menentukan dua kecamatan sebagai lokasi penelitian yaitu Kecamatan Tanjung Morawa dan Kecamatan Bangun Purba. Penentuan lokasi dilakukan secara purposive sampling berdasarkan populasi ternak ruminansia kecil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…While much attention has been focused on animal species raised in typical farm production settings, AMR in livestock from integrated livestock and agroforestry systems may also serve as a comparable source of AMR risks to animals, humans, and the environment (One Health approach). AMR in E. coli derived from ruminant livestock reared within this particular system, which is widely implemented across several regions of Indonesia [44][45][46]51], is limited. In the current study, most livestock farmers reported high antimicrobial usage on their farms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While much attention has been focused on animal species raised in typical farm production settings, AMR in livestock from integrated livestock and agroforestry systems may also serve as a comparable source of AMR risks to animals, humans, and the environment (One Health approach). AMR in E. coli derived from ruminant livestock reared within this particular system, which is widely implemented across several regions of Indonesia [44][45][46]51], is limited. In the current study, most livestock farmers reported high antimicrobial usage on their farms.…”
Section: Discussionmentioning
confidence: 99%
“…Agro-silvopastoral systems integrate the production of animals with trees and crops [42,43]. In North Sumatra Province [44,45], including Deli Serdang Regency [46,47], livestock production integrated with oil palms and forests has been reported. Crops and oil palm plantations predominate on agricultural land in this area, whereas goats, cattle, broilers, and laying chickens and pigs are the main animal producers [48].…”
Section: Demographic Characteristics Of the Farmsmentioning
confidence: 99%
“…Livestock rearing in plantation areas using an intensive system (cut and carry) does not hurt oil palm. An extensive system with livestock released in oil palm plantations can damage the main crop [14]. The presence of cattle in palm oil plantations is expected to control weeds on plantation land [15].…”
Section: Introductionmentioning
confidence: 99%